Video assisted thoracoscopy as a therapeutic modality in evacuating retained or clotted haemothoraces - Ambreen Abid; Tanveer Ahmad; Khalil Ahmed Shaikh; Shagufta Nasreen; Nazish Sikander; Misauq Mazcuri (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the role of VATS (Video Assisted Thoracoscopy) for evacuating retained / clotted haemothorax resulting in minimising the duration of chest tube drainage and length of hospital stay. Methods: From July 2019 to February 2020, 160 consecutive patients underwent VATS for retained or clotted haemothoraces at the Department of Thoracic Surgery, Jinnah Postgraduate Medical Centre. Institutional review board approval and consent from all patients taken. Outcome was measured as partial or complete lung expansion and relapse of collection. Results: There were 128 (80%) male and 32 (20%) female. 103 (64.37%) patients underwent VATS in first week (2-7) and 57 (35.63%) in second week (8-14 days). Of 103 patients who underwent VATS the first week, (71.9%) had complete lung expansion which was significantly higher compared to those who underwent VATS in second week (28,1%). Ninety-nine participants had chest tube removed in first week of VATS. Participants who underwent VATS in first week had shorter duration of stay (p=0.000). Conclusion: VATS is a safe, reliable and effective technique for the evacuation of retained haemothorax in haemodynamically stable patients. Early intervention within first week of injury not only is associated with better outcome but shorter duration of hospital stays. Keywords: VATS, blunt trauma, Clotted haemothoraces, Continuous...